Trovão: eu sou... entre a paz e a violência: um estudo sobre trovão - mente perfeita da biblioteca copta de Nag Hammadi - Pecora, Alethea Aires (2012)
This dissertation focuses on Thunder: Perfect Mind, cryptic writing found among the dozens of other titles (mostly unknown until then) that make up what is now called the Nag Hammadi Library, produced between the third and fourth centuries of our era. After a presentation of the latter, with the codex that make up (a task we set ourselves in the first chapter of this work), we propose an approach to Thunder, that offer a translation and a commentary on all the units that compose it (Chapter II). From here we review the opinions that have been issued regarding this writing, and especially question the characterization of the writing as a Gnostic (Chapter III). At the end we launched a few suggestions for a renewed approach of the writing, pointing to the possibility of a dual origin for it, sending it to both the mythical universe of Middle Eastern world as to the everyday of violence experienced particularly by women of that social-history context